Impairment of the proximal to distal tonic gradient in the human diabetic stomach. Issue 2 (25th October 2013) - Min, Y. W.; Hong, Y. S.; Ko, E.‐J.; Lee, J. Y.; Min, B.‐H.; Sohn, T. S.; Kim, J. J.; Rhee, P.‐L.
Abstract Background Little has been known about the contractile characteristics of diabetic stomach. We investigated spontaneous contractions and responses to acetylcholine in the gastric muscle in diabetic patients and non‐diabetic control subjects according to the region of stomach. Methods Gastric specimens were obtained from 26 diabetics and 55 controls who underwent gastrectomy at Samsung Medical Center between February 2008 and November 2011. Isometric force measurements were performed using circular muscle strips from the different regions of stomach under basal condition and in response to acetylcholine. Key Results Basal tone of control was higher in the proximal stomach than in the distal (0.63 g vs 0.46 g, p = 0.027). However, in diabetics, basal tone was not significantly different between the proximal and distal stomach (0.75 g vs 0.62 g, p = 0.32). The distal stomach of diabetics had higher basal tone and lower frequency than that of control (0.62 g vs 0.46 g, p = 0.049 and 4.0/min vs 4.9/min, p = 0.049, respectively). After exposure to acetylcholine, dose‐dependent increases of basal tone, peak, and area under the curve (AUC) were noticed in both proximal and distal stomach of the two groups. In the proximal stomach, however, the dose‐dependent increase of basal tone and AUC was less prominent in diabetics than in control. Conclusions & Inferences On the contrary to control, the proximal to distal tonic gradient was not observed in diabetic stomach. Diabetic stomach also had lower frequency of spontaneous contraction in the distal stomach and less acetylcholine‐induced positive inotropic effect in the proximal stomach than control.